2011
DOI: 10.1097/mnm.0b013e328345f8be
|View full text |Cite
|
Sign up to set email alerts
|

Impact of histopathology of non-neoplastic thyroid tissue on ablation outcome in patients with papillary thyroid cancer

Abstract: Histopathology of non-neoplastic thyroid tissue has a significant impact on ablation outcome in patients with PTC. Patients with a histopathology of non-neoplastic thyroid tissue of autoimmune origin have a significantly lower incidence of successful complete ablation after a single I-131 ablative dose (100 mCi) compared with those with nonautoimmune histopathology or with normal thyroid tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Inflammatory changes of thyroid tissue may also play a role. In a recent clinical study, high dose (3700 MBq) radioactive‐iodine remnant ablation demonstrated a lower success rate of 33.4% in patients with thyroiditis, whereas patients without thyroiditis had a success rate of 80% …”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory changes of thyroid tissue may also play a role. In a recent clinical study, high dose (3700 MBq) radioactive‐iodine remnant ablation demonstrated a lower success rate of 33.4% in patients with thyroiditis, whereas patients without thyroiditis had a success rate of 80% …”
Section: Discussionmentioning
confidence: 99%
“…The latter authors [17] reported an ablation outcome of 89.7% for 100 mCi (3700 MBq). These include remnant size, the given 131 I dose, stunning effect [19,20], 131 I uptake, tumor stage, and the histopathology of non-neoplastic thyroid tissue [14]. The difference in ablation outcomes reported by different authors is actually related to multiple factors that affect the ablation outcome and are interlinked with each other.…”
Section: Discussionmentioning
confidence: 99%
“…[10] . Maxon et al, 1992 [11] reported complete ablation in 86% of patients using initial dose of 100 mCi, Where (2006) Zaman et al reported an ablation rate of 54% was achieving the same dose [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have established the adequacy of low dose I131 in successfully ablating remnant thyroid in selected patients with a first ablation dose as low as 30-50 mCi [10] . To our knowledge no single study assessed the successful complete ablation rate post a second low ablation dose in patients who failed to achieve complete ablation after the first ablation dose.…”
Section: Introductionmentioning
confidence: 99%